PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS IX SMP NEGERI 14 PADANG SUMATERA BARAT - Zulfikarni,, M. Rafi Yasien, Irfani Basri, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This article was written to detect the influence of cooperative learning think pair share concerning short story writing skill of class IX students of SMPN 14 Padang. The data of this research were the result of the short story writing final test. The data were collected by giving short story writing test through cooperative learning think pair share and without cooperative learning think pair share. The hipotesis tested by using test-t formula. The result indicated that (1) the arithmetic average of the students’ short story writing skills pretest 54,14; (2) the arithmetic average of the students’ short story writing skills posttest were 82,65; and (3) according to test-t’s result, can be concluded that there was a significant influence of the used of cooperative learning think pair share to the short story writing skill of class IX students of SMPN 19 Padang.  Kata kunci: pengaruh, think pair share, menulis cerpen